Travel Experience on Travel Satisfaction and Loyalty of BRT Public Transportation - Nelloh, Liza Agustina Maureen; Handayani, Sri Handayani; Slamet, Mulyadi Wiguna; Santoso, Adhi Setyo (The Asian Journal of Technology Management (AJTM), 2019)
Abstract. As the only Bus Rapid Transportation (BRT) system public transportation in Jakarta, Indonesia, travel experience factors were important factor to enhance travel satisfaction and loyalty among passengers. However, travel experience is still rare to be tested among public transportation especially for BRT System Company. This study aims to test the travel experience factors (EF’s factors) such as individual space, information provision, staff’s skills, social environment, vehicle maintenance, off-board service, ticket line service, safety, and waiting time on travel satisfaction and customer loyalty. To test the hypotheses, this study employs Structural Equation Model-Partial Least Square with SmartPLS Version 3.0 among 294 passengers. The results shows that individual space, staff’s skills, vehicle maintenance, ticket line service are positively effect on travel satisfaction, then the travel satisfaction has positive influence on customer loyalty. Hence, social environment, off-board service, safety and waiting time have no influence on travel experience. The current findings suggest the government, and management of BRT to maintain the vehicle condition, improve the ticketing service use online system, recruit higher quality drivers, adding more staffs on-board, manage the schedule of buses, and adapt modern system of location. The society must also be educated to create conducive conditions during the travel trip.Keywords:  BRT System Company; Customer loyalty, Partial Least Square, travel satisfaction, travel experience